Identify the Saccharin Content in Iced Tea Sold in Jl. Sapta Marga, Sapta Marga Village, Mataram City - Wahyuningsih, Sri; Azwaruddin, Azwaruddin; Abdullah, Taufik (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Saccharin is an artificial sweetener made from sodium salt, sodium saccharin with the chemical formula C7H5NO3S from saccharin acid which is in the form of white crystalline powder, easily soluble in water, odorless and very sweet. Saccharin has a sweetness level of 300-600 times that of natural sweeteners. This artificial sweetener also has a maximum limit for its use, namely according to Bpom No. 11. In 2019, it is 954 mg/l. The aim of the research is to determine whether there is a saccharin compound present or not and to find out how much saccharin is contained in iced tea drinks circulating on the Sapta Marga road in the Mataram City area.Sampling uses predeterminet criteria. This type of research is descriptive qualitative. The analysis in this research was carried out in 2 types, namely qualitative analysis using the resorcinol color test method and quantitative analysis using the Uv-Vis spectrophotometry method. The results of qualitative identification using the color test method carried out on 5 samples of iced tea drinks did not produce positive samples so that all samples were not continued to the quantitative test stage.